Prognostic significance of the triglyceride-glucose index for patients with ischemic heart failure after percutaneous coronary intervention - Sun, Tienan; Huang, Xin; Zhang, Biyang; Ma, Meishi; Chen, Zheng; Zhao, Zehao; Zhou, Yujie (Frontiers in Endocrinology, 2023)
Background: In previous studies, the TyG index (triglyceride-glucose index) has been proven to be closely associated with the prognosis of cardiovascular disease. However, the impact of TyG index on the prognosis of patients with ischemic HF (heart failure) undergoing PCI (percutaneous coronary intervention) is still unclear. Method: In this study, 2055 patients with ischemic HF were retrospectively enrolled and classified into four groups based on quartiles of the TyG index. The primary endpoint was MACE (major adverse cardiovascular events) consisting of all-cause mortality, non-fatal MI (myocardial infarction), and any revascularization. The incidence of the endpoints among the four groups was assessed through Kaplan-Meier survival analysis. The independent correlation between TyG index and endpoints was analyzed with multivariate Cox regression models. Besides, the RCS (restricted cubic spline) analysis was performed to examine the nonlinear relationship between TyG index and MACE. Result: The incidence of MACE was significantly higher in participants with a higher TyG index. The positive association between the TyG index and MACE was also confirmed in the Kaplan–Meier survival analyses. Multivariate cox proportional hazards analysis indicated that the TyG index was independently associated with the increased risk of MACE, regardless of whether TyG was a continuous [TyG, per 1‑unit increase, HR (hazard ratio) 1.41, 95% CI (confidence interval) 1.22-1.62, P < 0.001] or categorical variable [quartile of TyG, the HR (95% CI) values for quartile 4 was 1.92 (1.48-2.49), with quartile 1 as a reference]. In addition, the nonlinear association of TyG index with MACE was shown through RCS model and the risk of MACE increased as the TyG index increased in general (Nonlinear p=0.0215). Besides, no obvious interaction was found in the association of TyG with MACE between the DM (diabetes mellitus) group and the no-DM group. Conclusion: Among patients with ischemic HF undergoing PCI, the TyG index was correlated with MACE independently and positively.